FETAL BILATERAL ADRENAL HEMORRHAGE: (case report) - Randhawa, J. S.; Nagamahendran, R.; Shankaran, R. (International Journal of Medicine and Medical Research, 2023)
Background. Fetal supra renal mass revealed incidentally by routine antenatal ultrasound is a great challenge for diagnosis and management by a surgeon. This is a matter of parental anxiety and diagnostic dilemma to a physician. Indeed, such masses turn out to be complicated by an intra-tumor hemorrhage in neuroblastoma or antenatally diagnosed adrenal hemorrhage. The first one needs intensive management and the latter needs watchful observation. Objective. A case of bilateral fetal adrenal mass revealed by routine fetal ultrasound examination at 28th week of gestation which turned out to be adrenal hemorrhage is presented. This is aimed to make awareness to ensure that clinicians always keep benign etiologies first and thoroughly investigate in case of incidentally detected fetal adrenal mass. Methods. The study is a single case report of incidentally revealed supra renal mass. This case report encompasses differentiating features between the two and investigations that aid the surgeon to avoid unnecessary intervention in a benign hemorrhage. Results. The baby was kept on follow up with serial ultrasound scans in the postnatal period and by the second scan in a month, the hemorrhage had resolved completely. Conclusion. In cases of benign looking masses like adrenal hemorrhage or spontaneously resolving neuroblastoma, appropriate antenatal assessment and close monitoring with serial ultrasound scans can avoid surgery.